Impact Corporate Taxpayer Compliance On Tax Revenue Growth With Tax Audit Moderation - Muhammad Yamin Noch; Entis Sutisna; Kartim; Septyana Prasetianingrum; Yaya Sonjaya (Jurnal Akuntansi, 2024)
This study examined the effect of tax audits and corporate taxpayer compliance on increasing tax revenue, focusing on corporate taxpayers at KPP Madya Makassar. A quantitative approach was employed, using secondary data collected from 12 corporate taxpayers annually from 2015 to 2018, resulting in 48 observations. Data analysis included descriptive statistical tests, classical assumption tests, and hypothesis testing through linear regression. The results indicated that while the Taxpayer Compliance Level and Tax Audit had positive coefficients, neither variable significantly affected tax revenue. Additionally, the interaction between Taxpayer Compliance and Tax Audit did not significantly moderate the impact on tax revenue. These findings suggest that although tax audits have a role in monitoring compliance, they do not substantially moderate the relationship between taxpayer compliance and tax revenue. This study provides valuable insights for tax authorities and policymakers in designing strategies to enhance compliance and optimise tax audits.